PENGARUH ARUS KAS OPERASI DAN LIKUIDITAS TERHADAP PROFITABILTAS (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI) Attin Munadhiroh - Attin Munadhiroh; Nurchayati Nurchayati (FEB UNTAG Semarang, 2015)
This study aims to determine the effect of operating cash flow as measured by the ratio of AKO and liquidity as measured by the current ratio to profitability as measured by return on equity in the property and real estate companies listed on the Stock Exchange. Data used in this research is secondary data, ie financial statements in 2013, while the samples used in this study was determined by clustered sampling method, so that the company obtained 32 samples.The analytical method used is descriptive analysis by describing the tables of Cash Flow Ratio (Operating Cash Flow), Liquidity (Current Ratio) and Profitability (Return on Equity) and inferential analysis using multiple regression analysis.The results of this study concluded: (1) Operating cash flow has a positive and significant impact on profitability with a significance level of 0.03 <0.05, (2) liquidity has a negative influence but not significant to profitability with a significance level of 0.766> 0.05.Keywords: Operating Cash Flow, Liquidity, Profitability